Modern IOS App Development with SwiftUI and Combine: A Declarative Approach to UI and State (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The landscape of iOS app development has undergone a paradigm shift with the introduction of SwiftUI and Combine, ushering in a declarative and reactive programming model that redefines how user interfaces are built and managed. This article explores modern iOS app development using SwiftUI and Combine, focusing on how these technologies enable a more intuitive, maintainable, and scalable architecture.SwiftUI allows developers to describe UIs declaratively, simplifying view composition and reducing boilerplate, while Combine introduces a robust framework for handling asynchronous events and data streams through publishers and subscribers. Together, they provide a unified approach to managing state, rendering views, and responding to user interactions.We delve into the core principles of declarative UI design, reactive state management, and data flow with Combine, illustrating how these tools work in tandem to produce dynamic and responsive iOS applications. Real-world development patterns, best practices, and practical use cases are examined to highlight how developers can leverage these frameworks to streamline development workflows and improve app performance.By the end of this article, readers will gain a comprehensive understanding of how to architect modern iOS apps that are both elegant and robust—using SwiftUI and Combine as foundational tools for building the next generation of Apple platform experiences.